Injury to the cornea due to fish bile. - Christoffersen, T.; Olsen, E. G. (Scandinavian Journal of Work, Environment & Health, 1993)
A retrospective study of 207 patients with chemical eye injuries in northern Norway revealed that fish bile was the causal agent in 14%. Fish bile caused superficial corneal erosions in 28 of 29 cases. All but one of the patients were professional fishermen or fish industry workers. In one case delayed medical care led to serious corneal opacity. Provided that there was immediate and abundant rinsing of the affected eye and good medical care, the prognosis of fish bile injuries was fairly good. The mechanisms for corneal damage due to fish bile are not clear.